Synthesis, antileishmanial activity and QSAR studies of 2-chloro- N -arylacetamides - Stefânia Neiva Lavorato; Mariana Costa Duarte; Pedro Henrique Rocha De Andrade; Eduardo Antonio Ferraz Coelho; Ricardo José Alves (Universidade de São Paulo, 2017)
ABSTRACT We describe herein the synthesis and evaluation of the antileishmanial activity against promastigote forms of Leishmania amazonensis and cytotoxicity to murine macrophages of a series of 2-chloro-N-arylacetamide derivatives. All compounds were active, except one (compound 3). Compound 5 presented the most promising results, showing good antileishmanial activity (CI50=5.39±0.67 µM) and moderate selectivity (SI=6.36), indicating that further development of this class is worthwhile. Preliminary QSAR studies, although not predictive, furnished some insights on the importance of electronic character of aryl substituent to biological activity, as well as an indirect influence of hydrophobicity on activity.